High‐Density Sb2Te3 Nanopillars Arrays by Templated, Bottom‐Up MOCVD Growth. Issue 37 (21st June 2019) - Cecchini, Raimondo; Gajjela, Raja S. R.; Martella, Christian; Wiemer, Claudia; Lamperti, Alessio; Nasi, Lucia; Lazzarini, Laura; Nobili, Luca G.; Longo, Massimo
Abstract: Sb2 Te3 exhibits several technologically relevant properties, such as high thermoelectric efficiency, topological insulator character, and phase change memory behavior. Improved performances are observed and novel effects are predicted for this and other chalcogenide alloys when synthetized in the form of high‐aspect‐ratio nanostructures. The ability to grow chalcogenide nanowires and nanopillars (NPs) with high crystal quality in a controlled fashion, in terms of their size and position, can boost the realization of novel thermoelectric, spintronic, and memory devices. Here, it is shown that highly dense arrays of ultrascaled Sb2 Te3 NPs can be grown by metal organic chemical vapor deposition (MOCVD) on patterned substrates. In particular, crystalline Sb2 Te3 NPs with a diameter of 20 nm and a height of 200 nm are obtained in Au‐functionalized, anodized aluminum oxide (AAO) templates with a pore density of ≈5 × 10 10 cm −2 . Also, MOCVD growth of Sb2 Te3 can be followed either by mechanical polishing and chemical etching to produce Sb2 Te3 NPs arrays with planar surfaces or by chemical dissolution of the AAO templates to obtain freestanding Sb2 Te3 NPs forests. The illustrated growth method can be further scaled to smaller pore sizes and employed for other MOCVD‐grown chalcogenide alloys and patterned substrates. Abstract : Sb2 Te3 nanostructures are grown by metal organic chemical vapor deposition (MOCVD) to form dense arrays: 20 nm single‐crystal Sb2 Te3 nanopillars are grown by MOCVD inside high density (5 × 10 10 cm −2 ) pores of aluminum oxide membranes. High‐density forests of freestanding Sb2 Te3 nanopillars are also obtained. These methods can be used for different chalcogenide alloys and substrates.